Results of myringoplasty operations in active and inactive ears in adults. (8th July 2013) - Mills, Robert; Thiel, Gundula; Mills, Nadtaya
Abstract : Objectives/Hypothesis: To determine whether the presence of aural discharge at the time of surgery adversely affects the success rate of myringoplasty operations. Study Design: Case series comparing the success rate of surgery in active and inactive ears. Methods: Data pertaining to 268 operations involving repair of the tympanic membrane without ossiculoplasty carried out in Edinburgh, United Kingdom, between 1999 and 2009 by one senior surgeon and trainees working under his supervision were collected prospectively. Other factors that might potentially influence the outcome of the surgery were investigated using logistical regression analysis. The main outcome measure was number of patients with an intact tympanic membrane 6 months after surgery in the two groups (active and inactive). Results: Of the 268 operations carried out, 203 were successful, with an intact tympanic membrane, 6 months postoperatively, 43 had persistent perforations, and 22 patients were lost to follow‐up before 6 months. The success rates for closure of the perforation at 6 months after surgery were 83% for inactive and 82% for active ears ( P = .9). Conclusions: There is no clinically significant difference in the success rate for myringoplasty in patients whose ears are active or inactive at the time of surgery. Level of Evidence: 4. Laryngoscope, 123:2245–2249, 2013